The Inessential Woman: A Beauvoirian Analysis of Female Otherness in Mueenuddin's Saleema - Tsabitah Ashilah; Ruly Indra Darmawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the construction of female identity and oppression in Daniyal Mueenuddin’s short story Saleema (2009) from the collection In Other Rooms, Other Wonders using Simone de Beauvoir’s existential feminist framework. Employing a descriptive qualitative method with a close textual reading approach, the research analyzes how patriarchal and feudal structures in Pakistani society restrict the female protagonist’s autonomy. The findings reveal that Saleema is constructed as the Other through sexual objectification and dependence on male authority figures. These conditions deny her autonomy and reinforce her subordinate position within patriarchal society. The study also explores the tension between transcendence and immanence in Saleema’s life. Although she briefly demonstrates transcendence through her personal choices, patriarchal and socioeconomic constraints ultimately force her back into immanence. As a result, her attempt to assert agency collapses into personal destruction and loss of subjectivity. This study concludes that Saleema’s fate reflects structural oppression rather than individual failure. It also contributes to feminist literary criticism by demonstrating the relevance of Beauvoir’s existential feminism in analyzing gender oppression and female subjectivity in Pakistani literature.